👤

[tex]a = \sqrt{11 + 4\sqrt{7} } \\b = \sqrt{11 - 4\sqrt{7} }[/tex]

A) a × b =
B) aratati ca [tex](a - b)^{2} = 16[/tex]


Răspuns :

[tex]a = \sqrt{11 + 4 \sqrt{7} } [/tex]

[tex]b = \sqrt{11 - 4 \sqrt{7} } [/tex]

[tex]A)a \times b = \sqrt{11 + 4 \sqrt{7} } \times \sqrt{11 - 4 \sqrt{7} } [/tex]

[tex]a \times b = \sqrt{(11 + 4 \sqrt{7} )(11 - 4 \sqrt{7} )} [/tex]

[tex]a \times b = \sqrt{ {11}^{2} - {(4 \sqrt{7} )}^{2} } [/tex]

[tex]a \times b = \sqrt{121 - 112} [/tex]

[tex]a \times b = \sqrt{9} [/tex]

[tex]a \times b = 3[/tex]

[tex]B) {(a - b)}^{2} = 16[/tex]

[tex] {(a - b)}^{2} = {( \sqrt{11 + 4 \sqrt{7} } - \sqrt{11 - 4 \sqrt{7} }) }^{2} [/tex]

[tex] {(a - b)}^{2} = {( \sqrt{11 + 4 \sqrt{7} } )}^{2} - 2 \sqrt{(11 + 4 \sqrt{7} )(11 - 4 \sqrt{7} )} + {( \sqrt{11 - 4 \sqrt{7} }) }^{2} [/tex]

[tex] {(a - b)}^{2} = 11 + 4 \sqrt{7} - 2 \times 3 + 11 - 4 \sqrt{7} [/tex]

[tex] {(a - b)}^{2} = 4 \sqrt{7} - 4 \sqrt{7} + 11 + 11 - 6[/tex]

[tex] {(a - b)}^{2} = 22 - 6[/tex]

[tex] {(a - b)}^{2} = 16[/tex]